Global pattern of leaf litter nitrogen and phosphorus in woody plants - Kang, Hongzhang; Xin, Zaijun; Berg, Björn; Burgess, Paul J.; Liu, Qunlu; Liu, Zhicheng; Li, Zhaohua; Liu, Chunjiang (EDP Sciences, 2010)
Forest ecosystems exert an important influence on global biogeochemical cycles. A global dataset of nitrogen (N) and phosphorus (P) concentrations in leaf- litter of woody plants was compiled from the literature. Among the 677 data sets, 482 included P concentrations and the N:P ratio. At a global scale, the mean leaf-litter N and P and N:P ratio were 10.9 mg g-1, 0.85 mg g-1 and 18.3, respectively. Leaf-litter N and P were significantly correlated. When the data was grouped by continents, the highest mean N was found in Africa (19.5 mg g-1), and the lowest in North America (8.18 mg g-1). P was significantly smaller in the Asian Islands (Japan and Malaysia, 0.44 mg g-1) than on the Asian mainland. For the global dataset, leaf-litter N increased linearly with mean annual temperature and annual precipitation and decreased with latitude. Although leaf- litter P showed no significant relationship with temperature, it declined linearly with precipitation and there was a convex quadratic relationship with latitude. For the global dataset and also for different functional groups (e.g. shrubs, evergreen broadleaf, deciduous broadleaf, and conifers) the leaf-litter N:P ratio generally followed a positive linear relationship with temperature and precipitation, and showed a concave quadratic response with latitude. The differences in leaf-litter N:P ratio among functional groups and among continents should be taken into account when modeling biogeochemical cycles in different regions as well as on a global scale.
Keywords: nitrogen phosphorus woody plants leaf-litter climate nutrient resorption stoichiometry chemistry latitude forest decomposition temperature leaves